The efficacy and potential mechanisms of pyrotinib in targeting EGFR and HER2 in advanced oral squamous cell carcinoma - Liang Zhou; Kehao Le; Qianming Chen; Huiming Wang (BMC, 2024)
Abstract Background Human epidermal growth factor receptor 2 (HER2) plays an important role in the progression of multiple solid tumors and induces resistance to epidermal growth factor receptor (EGFR) target treatment. However, the expression status and the clinical significance of HER2 in oral squamous cell carcinoma (OSCC) is still controversial. Pyrotinib (PYR) is a promising novel EGFR/HER2 dual inhibitor, whose efficacy in OSCC has not been determined. Methods 57 locally advanced de novo OSCC patients were included in this study to investigate the relationship between the HER2 expression levels and the prognosis by the tissue microarray analysis (TMA). In vitro and in vivo experiments were performed to retrieve the efficacy of PYR in OSCC. The main downstream of HER2 was evaluated by western blotting in OSCC cell lines and xenograft tumors to explore the potential mechanism of PYR. Results This study revealed the primary tumor of OSCC had higher HER2 expression levels. Patients with HER2 overexpression had poor overall survival (P < 0.014) and poor disease free survival (P < 0.042). In vitro, PYR suppressed the proliferation, colony formation and migration of OSCC cells. It also promoted apoptosis of OSCC cells and induced cell cycle arrest. Furthermore, PYR was able to inhibit the occurrence and development of OSCC effectively in vivo. Western blotting revealed that PYR suppressed OSCC by inhibiting the phosphorylation of HER2, AKT and ERK. Conclusions This study exhibited the anti-OSCC effects of PYR in vitro and in vivo, and demonstrated PYR inhibited OSCC cells by inducing apoptosis via the HER2/ AKT and ERK pathway. The result of this study also indicated locally advanced OSCC patients might benefit from HER2 assay and EGFR/HER2 dual inhibit treatment.